2022
DOI: 10.1155/2022/1380353
|View full text |Cite
|
Sign up to set email alerts
|

Administration of N-Acetylcysteine to Regress the Fibrogenic and Proinflammatory Effects of Oxidative Stress in Hypertrophic Ligamentum Flavum Cells

Abstract: Ligamentum flavum hypertrophy (LFH) is a major cause of lumbar spinal stenosis (LSS). In hypertrophic ligamentum flavum (LF) cells, oxidative stress activates intracellular signaling and induces the expression of inflammatory and fibrotic markers. This study explored whether healthy and hypertrophic LF cells respond differently to oxidative stress, via examining the levels of phosphorylated p38 (p-p38), inducible nitric oxide synthase (iNOS), and α-smooth muscle actin (α-SMA). Furthermore, the efficacy of N-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
1
0
0
Order By: Relevance
“…The GO analysis revealed that these lncRNAs were mainly associated with metabolic processes, organelles, nuclear lumen, cytoplasm, protein binding, nucleic acid binding, and transcription factor activity. These results are consistent with those of previous studies that have implicated alterations in cellular metabolism [ 32 ], organelle function [ 33 ], and transcriptional regulation [ 34 , 35 ] in LFH pathogenesis. Furthermore, the KEGG pathway analysis showed several signaling pathways that might be associated with the differentially expressed lncRNAs, including the hippo signaling pathway, nucleotide excision repair, SNARE interactions in vesicular transport, and the NF-kappa B signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…The GO analysis revealed that these lncRNAs were mainly associated with metabolic processes, organelles, nuclear lumen, cytoplasm, protein binding, nucleic acid binding, and transcription factor activity. These results are consistent with those of previous studies that have implicated alterations in cellular metabolism [ 32 ], organelle function [ 33 ], and transcriptional regulation [ 34 , 35 ] in LFH pathogenesis. Furthermore, the KEGG pathway analysis showed several signaling pathways that might be associated with the differentially expressed lncRNAs, including the hippo signaling pathway, nucleotide excision repair, SNARE interactions in vesicular transport, and the NF-kappa B signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…[84] NAC is a precursor of glutathione, which is converted to glutathione in vivo [85] and subsequently inhibits the expression of many oxidative and fibrotic markers and inflammatory mediators in hypertrophic LF cells, attenuating the adverse effects of oxidative stress on LF. [86,87] Moreover, inflammation of the cauda equina and nerve roots is often accompanied by LSS, [88] and NAC attenuates the longterm inflammatory response of the nerves and the toxic effects induced by free radicals, suggesting that NAC may be protective against the inflammatory nerve roots and cauda equina in LSS. [89,90] Similar to NAC, harpagophytum procumbens (HP) also plays an antioxidant role via the Nrf2/NQO-1 signaling pathway.…”
Section: Potential Antioxidant Strategies Of Lssmentioning
confidence: 99%